We don't like your type around here: Regional and residential differences in exposure to online hate material targeting sexuality. Issue 3 (4th March 2019) - Costello, Matthew; Rukus, Joseph; Hawdon, James
ABSTRACT: What factors are related to online targeting of hate material based to sexual orientation? This study addresses that question, utilizing a sample of 968 Internet users aged 15–36. Employing a logistic regression analysis, we find that social network usage, online antagonism, informal online social control, and a lack of online anonymity increase the likelihood of being targeted. Moreover, individuals living in the southern region of the United States are nearly three times as likely to be targeted by hate related to sexual orientation, whereas those living in rural areas are more than twice as likely to face such targeting.